Analysis of Slang Words in Song Lyrics by Megan Thee Stallion on Tina Snow Album - I Komang Sulatra; Ni Made Verayanti Utami; Ewik Wiartati, Desak Made (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
Sociolinguistics is the study of language related with social conditions, which is related to the general function of language as a means of communication. This study concern on the slang word found in Megan Thee Stallion song lyrics on Tina Snow album. The aims of this study are to find out the types of slang words and the process of creating slang words found in Megan Thee Stallion song lyrics on Tina Snow album. This study chose Tina Snow album by Megan Thee Stallion as data source. There were two theories used in analyzing the data, first the theory proposed by Kipfer and Chapman (2007: 8) to analyse the types of slang word, and to analyse the word formation process of creating slang word used theory by Mattielo (2008: 72-154). In analysing the data, this study used descriptive qualitative method. The result of this study shows that there are two types of slang found in Tina snow album by Megan Thee Stallion song lyrics namely, primary slang and secondary slang. In the types of slang this study found primary slang and secondary slang. In the word formation process of creating slang word, this study found 5 types from 15 types of word formation process, there are: compounding, reduplicatives, acronyms and initialisms, blending, clipping.